Kontruksi Pancing Cumi Nelayan Kelurahan Motto Kecamatan Lembeh Utara Kota Bitung - Karyanto Karyanto; Yuli Purwanto (Jurnal Airaha, 2022)
The potential for squid in the waters of the Lembeh Strait, Bitung City is overflow. So that potential is utilized by fishermen in Motto village, to catch squid. The purpose of this research was to study the construction and fishing technique of squid fishing gear in Motto Village. The method of data collection was done by interview and direct observation in the field by following the fishing activities directly and The analysis used is descriptive. The results showed that the construction of squid jigging are includng rope reels, main line, hook, swivel. The construction of the squid jigs was modified by adding a tin ballast which was attached to the body of the fishing line as well as functioning as a ballast, and at the end of the body of the fishing rod, radium from scotlet was installed. The technque of catching squid is assisted by turn on flasing ligt of green and white which is dipped on the sea surface to function as an attractor to collect squid making it easy to fishing.